When time is limb: a rare case of acute upper limb ischaemia - Ayob MA; Amran AM; Takim M; Yahaya R; Azizul Fadzli Wan Jusoh @ Ab. Rahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
Acute limb ischemia (ALI) is a medical emergency with a time-sensitive outcome. Acute upper limb ischemia (AULI) is less common than lower limb ischemia,and relatively few cases have been reported. It may cause significant disabilities and severe functional impairment even in the absence of overt tissue loss. Six hours window of presentation yielded a better outcome. However, diagnosing and treating within the time frame has always been a challenge. A high index of suspicion assisted with Doppler study in a limited-resources health centre is of sound importance as limb ischemia might be mimicked by other diseases. We illustrated a case of AULI with atypical presentation and successful revascularisation intervention.